Electrochemical synthesis of versatile ammonium oxides under metal catalyst-, exogenous-oxidant-, and exogenous-electrolyte-free conditions. Issue 22 (17th February 2021) - Yuan, Yong; Li, Liang-Sen; Zhang, Lin; Wang, Feng; Jiang, Lin; Zuo, Lin; Wang, Qi; Hu, Jian-Guo; Lei, Aiwen
Abstract : An electrochemical oxidative cross-coupling reaction between 2.5-substituted-pyrazolin-5-ones and ammonium thiocyanate has been developed. Abstract : An electrochemical oxidative cross-coupling reaction between 2.5-substituted-pyrazolin-5-ones and ammonium thiocyanate has been developed, which resulted in a series of unprecedented cross-coupling products under metal catalyst-, exogenous-oxidant-, and exogenous-electrolyte-free conditions. It is worth noting that since the resulting cross-coupling products are nearly insoluble in MeCN, the pure product could be afforded without silica gel column purification. In addition, the prepared ammonium oxides are versatile building blocks for synthesizing functionalized pyrazole derivatives.